From Being Served to Serving: How Servant Leadership Fosters Organizational Citizenship Behavior in the Digital Era - Huan Hong Nguyen; Cong Hiep Duong; Thi Trang Giang; Phuong Ngoc-Duy Nguyen (SAGE Open)
In the rapidly evolving business landscape and uncertain job market, particularly with the rise of non-traditional working methods, researchers have raised critical questions about how leadership impacts employees’ attitudinal and behavioral outcomes in the dynamic context. Our research addresses this call by exploring the impact of servant leadership (SL), a distinct leadership style from traditional methods, on organizational citizenship behavior (OCB), a pro-social behavior among employees in Vietnam. Additionally, we investigate how SL affects OCB, considering the mediating roles of technostress (TNS), psychological well-being (PWB), meaningful work (MOW), and organizational commitment (OC). This study employed a quantitative methodology, utilizing cross-sectional data collection from employees who have adopted NWoW in Vietnam. The research model was tested using the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach, given the study’s objective of predictive analysis with a complex research model. The study analyzed 380 valid responses, providing a representative sample to examine these research questions within its distinct cultural and social setting. The results indicate that PWB and MOW play significant mediating roles, whereas TNS and OC did not show significant mediation, prompting further investigation into the relationship between SL and OCB. In particular, the moderator roles of NWoW were highlighted. These findings offer valuable contributions to both the theory and practice of SL in the new working context, suggesting further research based on these intriguing findings. JEL Classification: J24, L29, O33.